2000
DOI: 10.1007/bf03031032
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and anatomy of mature embryos and seedlings in parasitic angiospermCuscuta japonica

Abstract: Morphological and anatomical features of mature embryos and seedlings were observed at different growth stages in the parasitic angiosperm Cuscutajaponica Choisy. The spirally coiled embryos from scarified seeds had no cotyledons but possessed blunt radicles. Seeds germinated at 30~ in the dark. Although most embryo cells incubated for 16 h did not have starch grains, the shoot cells of three-day-old seedlings possessed numerous starch grains. After these seedlings were transferred to a lightened growth chambe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…For example, in C. europaea it lacks both root cap and root apical meristem ( Fig. 1B and C) as observed by other authors (Lyshede 1986;Lee et al 2000;Behdarvandi et al 2015). Several days after germination this root-like organ degrades through a senescence-like process from apex towards the stem base ( Fig.…”
Section: Resultssupporting
confidence: 73%
“…For example, in C. europaea it lacks both root cap and root apical meristem ( Fig. 1B and C) as observed by other authors (Lyshede 1986;Lee et al 2000;Behdarvandi et al 2015). Several days after germination this root-like organ degrades through a senescence-like process from apex towards the stem base ( Fig.…”
Section: Resultssupporting
confidence: 73%
“…Although no starch-containing plastids exist in C. japonica embryonic cells (Lee, 2006), anatomical study has revealed that numerous starch grains are present in the subapical ground meristem cells of 3-d-old dark-grown seedlings (Lee et al, 2000). This feature was ultrastructurally confirmed here ( Fig.…”
Section: Plastidssupporting
confidence: 66%
“…4 in Lee et al, 2000), it may be assumed that those stored starch grains are digested and supplied to the embryo during the germination and early-growth stages. Second, starch grains in the subapical cells of the seedling shoot may result from certain biochemical pathway(s), e.g., gluconeogenesis, by which sugars are converted from lipid and protein bodies stored in the embryo cells (Li and Ross, 1990;Eastmond et al, 2000;Rylott et al, 2003;Cornah et al, 2004).…”
Section: Plastidsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was then scraped with a blade until the epidermal layer was reached (Ogundpie and Olatunji, 1991;Lee et al, 2000). The tissue was then washed in clean water and temporarily mounted in glycerin.…”
Section: Stomatal Patternsmentioning
confidence: 99%